Religion and politics: cultural perspectives - Giesen, Bernhard; Šuber, Daniel (International studies in religion and society 1573-4293, 2005)
The volume collects eminent works on the relationship between politics and religion by leading figures in Cultural Studies. The contributors share in the basic belief that the roots of contemporary conflicts have to be uncovered from the historical descent of religion